The Roles of Transformational Leadership on Employee’s Job Satisfaction, Readiness for Change, and Organizational Commitment of Islamic Banking in Indonesia - Ayu Putri Aprileani; Ferryal Abadi (Indonesian Journal of Business Analytics, 2022)
This study aims to deeply analyze the effect of transformational leadership, job satisfaction, readiness for change, and organizational commitment on work performance in Islamic banks. In this study, 195 respondents were obtained from Islamic bank employees in Indonesia based on a purposive sampling method by distributing online questionnaires. The research was conducted using a quantitative approach and processed by the Structural Equation Modelling method using the Lisrel application. The results showed that transformational leadership positively affects job satisfaction, readiness for change, and organizational commitment. However, transformational leadership, job satisfaction, and organizational commitment do not affect work performance. On the other hand, the study proves that readiness for change can be an intervening mediator in the research. This finding is a managerial implication that contributes to improving the work performance of Islamic bank employees through a commitment to instilling organizational values and providing adequate space to encourage self-development to increase employee satisfaction, organizational commitment, and work performance.